Pola Peningkatan Hasil Tanaman Jarak Pagar (Jatropha curcas L.) Ekotipe Lombok Barat selama Empat Tahun Siklus Produksi - Bambang Budi Santoso (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
The aim of this experiment was to evaluate the pattern of yield improvement of Jatropha curcas L. of West Lombokecotype at dry land of North Lombok, West Nusa Tenggara during four years production cycle. The experiment was conductedin randomized complete block design (RCBD) using three types of propagules (i.e., stem cutting, seed, and seed followed bypruning after transplanting) and three replications from November 2006 to November 2010. The results showed that yieldwas increased as plant age increased. Plants cultivated during rainy season had higher yield compared to those cultivatedduring dry season. However, the oil content of nuts was slightly higher when harvested in dry season than in rainy season.Yield was also affected by plant material used. In the fi rst year, plants propagated by stem cutting had the highest yield. Inthe second, third, and fourth year, plants propagated from seed followed by pruning produced the highest nut dry weight.During four years production cycle, yearly yield improvement was about 2-3 times than the previous year and did not followthe geometrical progression based on dichotomy branching pattern of Jatropha.Keywords: dry land, productivity, pruning, seed oil content, type of propagule